(untitled) (KULT_online, 2025)
The international conference on “The Social Impact of Land and Knowledge: Transformation of Land Distribution, Utilization in Post-colonial Southern Africa” took place between September 23 and 27, 2024, at the University of Fort Hare in East London and was co-organized with the Justus Liebig University. The goal was to address contemporary questions and challenges of land distribution and its various conditions in Southern African countries. For this purpose, scholars from Botswana, Namibia, South Africa, Nigeria, and Germany were invited to discuss notions of land rights, political discourses on land, food sovereignty and food security, and postcolonial challenges. In addition to the presentations, organizers arranged a field trip with Loliwe Bonani to visit an informal settlement.